1992
DOI: 10.1007/bf00400480
|View full text |Cite
|
Sign up to set email alerts
|

A high linear growth is associated with an increased risk of childhood diabetes mellitus

Abstract: Summary. Insulin release and growth are intimately connected. The aim of the present study was to investigate height and weight in diabetic children from birth to onset of Type 1 (insulin-dependent) diabetes mellitus compared to that in referent children. Data on height and weight were collected from mailed questionnaires and from growth records obtained from the child health clinics and schools in 337 recentonset diabetic children, 0-14 years old, and from 517 age-, sex-, and geographically matched referent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
77
4
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 22 publications
16
77
4
4
Order By: Relevance
“…Increased height and linear growth in childhood have been reported to be a risk factor for diabetes [17][18][19]. In the present study we failed to confirm an increased height based on SDS in children developing diabetes.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Increased height and linear growth in childhood have been reported to be a risk factor for diabetes [17][18][19]. In the present study we failed to confirm an increased height based on SDS in children developing diabetes.…”
Section: Discussioncontrasting
confidence: 87%
“…Retrospective studies of children with diabetes have reported increased linear growth up to 7 years before onset of disease [17] as well as increased height and weight standard deviation scores (SDS) from 1 month of age [18] and increased growth in length between 1 and 3 years of age [19,20]. The authors of the latter study corrected growth for mid-parental height (MPH), which is known to correlate with both birthweight and birth length [21], and with postnatal growth of the child [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The diffeIence was seen at 3 months of age and was statistically significant at 6, 9, 18 and 30 months. Similar results were seen in the study by Baum et al [10] while our findings are somewhat different from those of Blom et al [11] who did not show any difference in weight for age between diabetic and referent children from birth to clinical onset of Type 1 diabetes. They found however that boys who developed diabetes were consistently taller than referent boys from birth.…”
Section: Discussioncontrasting
confidence: 58%
“…Baum et al [10] compared diabetic and nondiabetic children regarding weight gain during the first year of life and found that children who develop Type 1 diabetes are heavier at certain stages in infancy. Blom et al [11] concluded from an incident case referent study that children (especially boys) who later develop diabetes tend to be slightly but consistently taller, although not heavier, than matched referent children from early childhood up to the year of clinical onset of Type 1 diabetes.…”
mentioning
confidence: 99%
“…These include viral infections [39][40][41], dietary factors (cow's milk, nitrosamines, high protein intake) [42,43], neonatal jaundice and ABO incompatibility [44], neonatal respiratory disease [44], early supplementary milk-based feeding, short time of breast-feeding [42,45] and stress events such as severe life events [42,46,47]. Several studies have found that children who later develop diabetes have a higher BW than controls, and also have an increased linear growth in childhood [15,16,42,48,49]. Our finding that HLA genetic factors, which are associated with susceptibility for type 1 diabetes, are related to intrauterine growth might in fact contribute to the increased BW in type 1 diabetes children.…”
Section: Discussionmentioning
confidence: 99%